Penerapan Ice Breaking untuk Meningkatkan Motivasi Belajar Bahasa Indonesia Siswa Kelas VII di SMP Negeri 13 Surakarta - Qatrunada, Himma; Susanti, Sinta Ari (Yudha English Gallery, 2023)
This study aims to evaluate the effectiveness of using the ice breaking technique in enhancing motivation and performance of seventh-grade students in learning Indonesian language at SMP Negeri 13 Surakarta. Data collection methods employed include observation and documentation. Observation was actively conducted by the researcher to monitor the learning process and the utilization of ice breaking by teachers. Documentation techniques such as questionnaires, tests, field notes, and observation sheets were utilized to monitor students' learning motivation and the implementation of ice breaking. Data analysis was conducted both qualitative and quantitative. The subjects of the study included seventh-grade students and teachers implementing ice breaking. The research findings indicate a significant improvement in students' learning motivation following the implementation of ice breaking. In the first cycle, only 20 out of 45 students achieved high motivation scores, whereas in the second cycle, 90% of students attained very high motivation scores. The average student motivation score also increased to 84 in the second cycle. Ice breaking has brought about positive effects by enhancing students' enthusiasm and concentration, consequently improving their learning performance.